Taxonomic assessment and biotechnological potential of yeasts hold at the Unesp - Central for microbial resources - Dayo-Owoyemi, Ifeloju [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Atualmente, existe um crescente interesse em explorar diversos habitats, a fim de revelar a biodiversidade microbiana, incluindo as leveduras. Tal diversidade ainda não acessada guarda a descoberta de novas espécies para ciência, provavelmente muitas das quais com potencial para aproveitamento em processos biotecnológicos. Com o objetivo de explorar e conservar a diversidade de fungos, o Central de Recursos Microbianos da UNESP (CRM – UNESP) mantém em seu acervo várias estirpes de leveduras isoladas de ecossistemas diversos, sendo alguns deles pouco explorados. No início deste trabalho sabíamos que muitas das leveduras depositadas no acervo do CRM – UNESP não estavam totalmente caracterizadas tanto em nível taxonômico, quanto em relação ao potencial biotecnológico que poderiam apresentar. Portanto, o presente estudo foi desenhado para caracterizar e identificar taxonomicamente leveduras depositadas no CRM – UNESP, bem como selecionar estirpes que produzem enzimas extracelulares degradadoras de polissacarídeos como amilase, celulase, xilanase, pectinase e ligninase. Usando uma abordagem polifásica, um total de 340 isolados de leveduras foi identificado, sendo que 71,2% compreendem 43 taxa de ascomicetos e os restantes 28,8% foram classificados em 27 taxa de basidiomicetos. O estudo também levou à descoberta de 8 prováveis novas espécies. Baseado nesta constatação, a classificação taxonômica e análise filogenética foi realizada para duas espécies anamórficas de ascomicetos e uma espécie teleomórfica de basidiomiceto. A descrição destas três espécies é apresentada neste estudo. Os resultados demonstraram que Wickerhamiella kiyanii FB1-1DASPT e W. pindamonhangabaensis H10YT pertencem à clade Wickerhamiella da ordem Saccharomycetales...

In recent time, there has been an increasing interest in exploring diverse ecological habitats in order to reveal the yeast biodiversity. The increased awareness in the biotechnological potentials of yeasts has also spurred attempts to search for new species with novel biotechnological capabilities. Aiming to explore and conserve the fungal diversity from various ecosystems, the UNESP – Central for Microbial Resources (UNESP – CMR) harbors various strains of ecologically diverse yeasts isolates, some of which were yet to be identified. Therefore, this study was designed to identify and characterize some yeasts from the UNESP – MRC and to select strains possessing extracellular plant polysaccharide degrading enzymes namely amylase, cellulase, xylanase, pectinase and ligninase. Using a polyphasic approach, a total of 340 strains were identified. Taxonomic classification grouped 71.2% of these isolates into 43 ascomycetous taxa while the remaining 28.8% were classified in 27 basidiomycetous taxa. The study also led to the discovery of 8 putative new species. As a result, we classified two anamorphic species in the Ascomycota and one teleomorphic species in the Basidiomycota. In this study we provide the description of both species. Our results demonstrated that the two ascomycetous species proposed as Wickerhamiella kiyanii FB1-1DASPT and W. pindamonhangabaensis H10YT belong to the Wickerhamiella clade of the Saccharomycetales (Saccharomycetes) while the basidiomycetous species proposed as Bulleromyces texanaensis ATT064T belong to the Bulleromyces / Papiliotrema / Auriculibuller clade of the Tremellales (Agaricomycotina). In order to show the significance of intraspecific diversity in yeasts, in one of our studies, we subjected 11 strains, (including the type strain CBS 8960T) of Hannaella kunmingensis... (Complete abstract click electronic access below)
Keywords: Biotechnology; Biotecnologia; Biodiversidade; Taxonomia vegetal; Levedos; Polissacarideos; Enzimas